Space workers : making money above Earth - Jefferis, David (New York : Crabtree Publishing Company, 2018)
Can't find a job on Earth? This book looks at the possibilities of industry and commerce in space. Artwork illustrates the scientific possibilities of mining asteroids and moons, setting up factories in space, designing new products for zero gravity, and even starring in your own reality show in space.
Signals around the world -- Assembling a satellite -- Observing Earth -- Finding the way -- The rocketeers -- Aerospace machines -- Junkyard in space -- Made in space -- Space suits -- Robots at the ready -- Space medicine -- Moon miners -- Unlimted future?
Includes bibliographical references (page 31) and index.
8.7
5-8
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Astronautics -- Juvenile literature; Space sciences -- Juvenile literature; Outer space -- Experiments -- Juvenile literature; Astronautics; Space sciences; Outer space -- Experiments